2023
DOI: 10.3390/ijerph20075359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Physical Activity Interventions on Sleep and Sedentary Time in Pregnant Women

Abstract: Pregnancy is often associated with poor sleep and high sedentary time (SED). We investigated the effect of physical activity (PA) interventions on sleep and SED in pregnant women. A secondary analysis of a randomized controlled trial (n = 219) explored the effect of structured supervised exercise training (EXE) or motivational counseling on PA (MOT) compared to standard prenatal care (CON) on sleep and SED during pregnancy. Three times during pregnancy, sleep was determined by the Pittsburgh Sleep Quality Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…These data are also consistent with systematic reviews of SED reduction interventions in non-pregnant populations that find interventions focused on SED reduction rather than increasing physical activity are more effective at reducing SED and that interventions including environmental-level components (e.g., height-adjustable workstations) are most effective and typically reduce SED by ~ 1 h per day [ 47 , 48 ]. This notion is reinforced in the recent Danish FitMum Study ( n = 220) that found fitbit-measured SED across pregnancy was not impacted by either a supervised exercise intervention or a motivational counselling on physical activity intervention (neither of which specifically targeted SED) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data are also consistent with systematic reviews of SED reduction interventions in non-pregnant populations that find interventions focused on SED reduction rather than increasing physical activity are more effective at reducing SED and that interventions including environmental-level components (e.g., height-adjustable workstations) are most effective and typically reduce SED by ~ 1 h per day [ 47 , 48 ]. This notion is reinforced in the recent Danish FitMum Study ( n = 220) that found fitbit-measured SED across pregnancy was not impacted by either a supervised exercise intervention or a motivational counselling on physical activity intervention (neither of which specifically targeted SED) [ 49 ].…”
Section: Discussionmentioning
confidence: 99%